Targeting protein synthesis pathways in MYC-amplified medulloblastoma - Devendra Kumar; Ranjana Kanchan; Nagendra K. Chaturvedi (Discover Oncology)
Abstract MYC is one of the most deregulated oncogenic transcription factors in human cancers. MYC amplification/or overexpression is most common in Group 3 medulloblastoma and is positively associated with poor prognosis. MYC is known to regulate the transcription of major components of protein synthesis (translation) machinery, leading to promoted rates of protein synthesis and tumorigenesis. MTOR signaling-driven deregulated protein synthesis is widespread in various cancers, including medulloblastoma, which can promote the stabilization of MYC. Indeed, our previous studies demonstrate that the key components of protein synthesis machinery, including mTOR signaling and MYC targets, are overexpressed and activated in MYC-amplified medulloblastoma, confirming MYC-dependent addiction of enhanced protein synthesis in medulloblastoma. Further, targeting this enhanced protein synthesis pathway with combined inhibition of MYC transcription and mTOR translation by small-molecule inhibitors, demonstrates preclinical synergistic anti-tumor potential against MYC-driven medulloblastoma in vitro and in vivo. Thus, inhibiting enhanced protein synthesis by targeting the MYC indirectly and mTOR pathways together may present a highly appropriate strategy for treating MYC-driven medulloblastoma and other MYC-addicted cancers. Evidence strongly proposes that MYC/mTOR-driven tumorigenic signaling can predominantly control the translational machinery to elicit cooperative effects on increased cell proliferation, cell cycle progression, and genome dysregulation as a mechanism of cancer initiation. Several small molecule inhibitors of targeting MYC indirectly and mTOR signaling have been developed and used clinically with immunosuppressants and chemotherapy in multiple cancers. Only a few of them have been investigated as treatments for medulloblastoma and other pediatric tumors. This review explores concurrent targeting of MYC and mTOR signaling against MYC-driven medulloblastoma. Based on existing evidence, targeting of MYC and mTOR pathways together produces functional synergy that could be the basis for effective therapies against medulloblastoma.